'All that doesn't make headlines': Responses to Zanu-PF's imaginaries of belonging in recent fiction from Zimbabwe. Issue 1 (2nd January 2017) - Ndlovu, Thabisani
ABSTRACT: With the ruling Zanu-PF's stranglehold on Zimbabwean media, and the same party's intolerance for dissent, literature has become part of the country's public sphere in contesting the ruling party's exclusivist imaginaries of belonging. Such literature, and some of its publishing methods, offer alternative possibilities that suggest a need to re-open the terms of national belonging, thus troubling categories such as race and ethnicity in what can be called a politics of recognition. In many ways, Bryony Rheam's This September Sun, writings by John Eppel, and the late Julius Chingono in Together, some of the short stories in Where to Now? Short Stories from Zimbabwe, and NoViolet Bulawayo's We Need New Names ask what has happened to ideas of tolerance, reconciliation, inclusivity and human diversity in Zimbabwe. Through various strategies of indirection, Zimbabwean writers present counter-discursive voices that suggest alternative and inclusive imaginaries of nationhood.